Educação Ambiental para o consumo sustentável: uso da pegada ecológica como recurso didático - Manhiça, José Aurélio (2020)
Any consumption pattern practiced by society has an associated environmental cost, since it costs nature to use soil areas, water volumes, as well as air quality and other environmental resources. Industrial activity is identified as the main responsible for global warming, due to the excessive use of fossil fuels, which with the burning causes the emission of gases that accelerate the greenhouse effect. Linked to this, the programmed obsolescence strategy of the products, in addition to contributing to the production of huge quantities of waste that pollute and contaminate rivers, seas, groundwater and soils, give rise to the indiscriminate use of natural resources, which compromises the regeneration capacity of ecosystems. This scenario becomes even more worrying, when looking at the “rules” of coexistence in contemporary society, where acceptance and social affirmation are dependent on the ability to keep pace with the fashion market, where products are constantly updated. In this sense, several educational initiatives have been carried out to promote sustainable consumption, in which the Ecological Footprint (EF) stands out, as a tool that, based on individual and / or collective lifestyle, calculates the amount of land and water needed to produce resources and still assimilate the waste produced, considering the technology involved. The present work analyzed the sustainability of the consumption habits of participants in the EF extension project between UFU students and external participants, through the application of a questionnaire on the EF electronic calculator, and questions related to the consumption of natural resources to reflect on the demands of the project participants, as a way to induce greater environmental concern in their lifestyles. As a result, it was observed that even though concerns are observed in many aspects, the need to change the behavior of the participants regarding the use of natural resources is defended. Environmental education assumes a primary role in pedagogical action in raising society's awareness of environmental issues, so that everyone is a protagonist of the necessary change in preserving the environment. Even with a certain mastery over issues related to environmental sustainability, the consumption practiced seems unsustainable, which according to the data, 1.9 Earth planets would be needed to continuously support the revealed footprint of the participants. For this reason, but rather than discussing situations that are often distant from the reality of the individual, the Ecological Footprint methodology proves to be quite interesting to promote reflections around the demands themselves. The essence of this tool is to reveal how much natural resources the planet produces, and how much can be extracted without compromising the capacity of ecosystems to make the replacement. EF appears as a very valuable teaching resource to promote reflection based on consumption habits, considering the supply chain of goods and services used in daily life.